Studi Penggunaan Pecahan Dinding Bangunan pada Beton Aspal Lapis Aus - Lie Ing Tan; Yohanes Sebastian (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
Pavement has become important to people mobility in Indonesia, especially in urban areas. Vehicle mobilization will experience less obstacles if the road pavement conditions are in good quality. At the moment, additives, fillers or road material substitutes are quite expensive and are limited, therefore, research needs to be carried out to find materials which can improve the quality of pavement such as increasing its resistance or stability and flow. The purpose of this study was to analyze the benefits of using wall fragments as the fillers in asphalt concrete wearing course. The effect of using wall fragments as a substitute for rock ash on the value of Marshall parameters is studied, as well as the various levels of wall fragments addition that can produce the greatest stability. In this study, four levels of wall fragments were used as fillers: 0%, 25%, 50% and 100%. Based on the results analysis, it was concluded that the use of wall fragments as fillers in asphalt concrete can increase the following parameters: VMA, VIM, stability, and flow, but it reduces the VFB value. In addition, the use of 25% levels of wall fragments in asphalt concrete produces the greatest stability value, which is 1622.47 kg.